2021
DOI: 10.17221/236/2021-pse
|View full text |Cite
|
Sign up to set email alerts
|

Exogenously spermidine alleviates damage from drought stress in the photosystem II of tall fescue

Abstract: Drought stress is one of the major limiting factors to crop productivity around the globe. It has been well documented that spermidine (Spd) plays an important key role in plant growth and development, especially in the defense response to stress. The objective of this study was to explore the effect of Spd on protecting photosynthetic apparatus in tall fescue under drought stress. Spd application significantly improved the OJIP (fluorescence rise kinetics O-J-I-P) curve compared to non-Spd application during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…After recovery, the S m values in all varieties reached the control values. The decrease in S m upon drought, as well as the positive H band (Figure 1d,i), suggested that Q A could be reduced but not re-oxidized, since it cannot perform multiple turnovers as fast as the control seedlings due to the limited electron transport [95,96].…”
Section: Changes In Jip-test Parameters After Drought and Recoverymentioning
confidence: 99%
“…After recovery, the S m values in all varieties reached the control values. The decrease in S m upon drought, as well as the positive H band (Figure 1d,i), suggested that Q A could be reduced but not re-oxidized, since it cannot perform multiple turnovers as fast as the control seedlings due to the limited electron transport [95,96].…”
Section: Changes In Jip-test Parameters After Drought and Recoverymentioning
confidence: 99%
“…In order to make it easier to analyze and more clearly represent the possible changes caused by the agents added to the control (in the absence of other additives); in comparison with the control, normalization is carried out to the initial level of fluorescence F 0 , as a rule, by the value of F 20µs or F 50µs measured at 20 µs or 50 µs, respectively [28], but sometimes by the F 0 value measured at time t = 0 [45,46]. In recent years, normalization to F 0.05ms has been favored, although normalization to F 0.02ms is acceptable and still quite common [47,48]. In addition, it is shown that the possible errors in the calculation of the parameters of the JIP test in the case when F 50µs is used as F 0 is higher than for F 20µs and F t →0 [45].…”
Section: Original Ojip Kinetics Normalized Relative To F 0 (F 002ms )mentioning
confidence: 99%